PENGEMBANGAN VIDEO ANIMASI BERBASIS DORATOON PADA MATERI PENGELOMPOKKAN HEWAN BERDASARKAN JENIS MAKANANNYA KELAS V SEKOLAH DASAR - ramadhani, rahmat; Kuntarto, Eko; Noviyanti, Silvina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: (1) describe the stages of developing Doratoon-based animated video learning media in IPAS class V elementary school subjects; (2) describe the level of validity of the media; and (3) explain the practicality of the media in delivering animal grouping material based on the type of food. The research used the Research and Development (R&D) method with the DDD-E model (Decide, Design, Develop, Evaluate). The research subjects were fifth grade students of SDN 14/I Sungai Baung. The data collection instrument was a questionnaire, with qualitative and quantitative data analysis techniques. The results showed that the media development followed the flow of the DDD-E model systematically. The validity of the media is classified as very high based on the assessment of material, language, and media experts, with the average final score reaching 4.64; 4.9; and 4.61, respectively, which is categorized as very valid. The practicality of the media is also evident from the positive responses of teachers and students. Doratoon media is designed to be interesting and interactive, increasing students' interest in learning. The small group trial resulted in an average score of 3.54 and large group 4.4, indicating this media is very practical to use. This media helps students understand the material more effectively and enjoyably although it still needs a little refinement in the visual aspect.